Nearby teachers (Journal of Parents and Teachers, 2024)
The author reflects on the importance of trust and care in the teacher-student relationship. He highlights that to achieve an education based on values such as tolerance, respect and inclusion, it is essential to foster closeness and human support. He suggests that his work should focus on three fundamental pillars: care, example and service, which he considers crucial for students to grow with self-esteem and solidarity.
Keywords: trust; care; values; support